[Campsite at Laugar] - Streng, Evelyn Fiedler (1975)
Photograph of a campsite at Laugar. Many yellow, orange, white, and blue tents sit along a green grass field. A grey stone wall is visible along the field to the right. A house with a red base, white walls, and three brown roofs sits on a hill in the background. Similar buildings line the foot of the large hill in the background. Groups of people stand beside tents throughout the field.